2018
DOI: 10.1007/s12098-018-2714-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Childhood Vaccine Refusal and Hesitancy Intentions in Turkey

Abstract: This is the first study conducted to investigate the social-demographic characteristics and perception of parental CVRH in Turkey. The beliefs "It may be dangerous for the children" and "Distrust the vaccines" were the most determined factors which may affect CVRH. Some child health protective strategies were less undertaken in CVRH group than in controls; including heel stick test, hearing test, using baby car seat and using of Vitamin D and iron prophylaxis. The parents who have CVRH intentions tend to behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 23 publications
1
20
0
7
Order By: Relevance
“…In one study from the US, parents were found to get their information about vaccines from health workers, followed by print materials such as books and magazines, and friends and relatives, and it was revealed that about half of families used the internet as their source of information (28). Although television, radio, and newspapers were mentioned as the sources of information in some studies, internet and social media are becoming more and more popular as an source of information on vaccines (13,29). On the other hand, only 3.0% of the content about vaccines on the internet was found to be created by health professional (30).…”
Section: Discussionmentioning
confidence: 99%
“…In one study from the US, parents were found to get their information about vaccines from health workers, followed by print materials such as books and magazines, and friends and relatives, and it was revealed that about half of families used the internet as their source of information (28). Although television, radio, and newspapers were mentioned as the sources of information in some studies, internet and social media are becoming more and more popular as an source of information on vaccines (13,29). On the other hand, only 3.0% of the content about vaccines on the internet was found to be created by health professional (30).…”
Section: Discussionmentioning
confidence: 99%
“…This study is the first national report on vaccine refusal in Turkey. Previous publications include surveys conducted on families or doctors, covering only a few hospitals in one or two provinces [ 10 , 14 , 62 ]. Additionally, the populations of these studies included only families already receiving health care or presenting at hospital because of a health problem.…”
Section: Discussionmentioning
confidence: 99%
“…The salary deduction of the FP is reimbursed if there is no negligence. Despite these implementations, an increase in cases of vaccine refusal has been observed in recent years in Turkey [ 14 , 15 ]. The prevalence of unvaccinated children aged 15–26 months increased from 1.6 to 2.9% between the Turkish Demographic Health Surveys (TDHS) of 2008 and 2013 [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Çalışmamızda üniversitede çalışan hekimlerde %10'a yakın aşı tereddüdü görülmesi üzerinde durulması gereken bir (16). Sağlık çalışanları, özellikle hekimler aşılarla ilgili her başvuruda bağışıklama sorgusuyla güvenilir bilgi kaynağı olarak modern tıbbın savunucusu olmalıdır.…”
Section: İrdelemeunclassified